Stability of Fried Olive and Sunflower Oils Enriched with Thymbra capitata Essential Oil - Miguel, Maria Graça (2015)
The stability of olive and sunflower oils for domestic uses after frying cow steak or only heating were evaluated in the presence or absence of the carvacrol-rich essential oil of Thymbra capitata. The treatments consisted of sunflower and olive oils either enriched with 200 mg/l of T. capitata oil or without it, heating at 180°C for 20 min, or frying 100 g cow steak at the same temperature and for the same period of time. In all assays, acid, peroxide, and p-anisidine values were followed over time. The fatty acid profile was estimated before heating or frying as well as at the end of the experiment. The results showed that the type of fat as well as the type of treatment (frying or heating) was determinant for the acid, peroxide, and p-anisidine values found. The presence of the essential oil also demonstrated to affect those values depending on the type of the oil as well as on the type of the treatment (frying or heating). In contrast, the fatty acid profile did not change greatly.